First-Year Establishment, Biomass and Seed Production of Early vs. Late Seral Natives in Two Medusahead (Taeniatherum caput-medusae) Invaded Soils. (June 2014) - Uselman, Shauna M.; Snyder, Keirith A.; Leger, Elizabeth A.; Duke, Sara E.
Abstract: Re-seeding efforts to restore or rehabilitate Great Basin rangelands invaded by exotic annual grasses are expensive and have generally achieved limited success. There is a need to identify new strategies to improve restoration outcomes. We tested the performance of a native early seral seed mix (annual forbs, early seral grasses and shrubs) with that of a native late seral mix representative of species commonly used in restoration when growing with medusahead in soils of contrasting texture (sandy loam and clay loam) through the first growing season after seeding. Natives were also seeded without medusahead. We found that the grasses and forbs in the early seral mix established significantly better than those in the late seral mix, and the early seral mix significantly reduced aboveground biomass and seed production of medusahead by 16 and 17% respectively, likely because of competition with the early seral native forb, bristly fiddleneck. Medusahead performance was reduced in both soil types, suggesting utility of bristly fiddleneck in restoration is not limited to only one soil type. In contrast, the late seral mix did not suppress medusahead establishment, aboveground biomass or seed production. Although the native perennial grasses, particularly early seral species, were able to establish with medusahead, these grasses did not appear to have a suppressive effect on medusahead during the first growing season. Medusahead was able to establish and produce seeds on both soil types, demonstrating an ability to expand its current range in the Intermountain West, though aboveground biomass and seed production was higher in the clay loam. Our results suggest that certain species may play a key role in restoration, and that targeting early seral species in particular to find additional native species with the ability to suppress exotic annual grasses is an important next step in improving restoration outcomes in desert ecosystems.